Novel surface-enhanced Raman scattering-based assays for ultra-sensitive detection of human pluripotent stem cells. (October 2016) - Han, Jingjia; Qian, Ximei; Wu, Qingling; Jha, Rajneesh; Duan, Jinshuai; Yang, Zhou; Maher, Kevin O.; Nie, Shuming; Xu, Chunhui
Abstract: Human pluripotent stem cells (hPSCs) are a promising cell source for regenerative medicine, but their derivatives need to be rigorously evaluated for residual stem cells to prevent teratoma formation. Here, we report the development of novel surface-enhanced Raman scattering (SERS)-based assays that can detect trace numbers of undifferentiated hPSCs in mixed cell populations in a highly specific, ultra-sensitive, and time-efficient manner. By targeting stem cell surface markers SSEA-5 and TRA-1-60 individually or simultaneously, these SERS assays were able to identify as few as 1 stem cell in 10 6  cells, a sensitivity (0.0001%) which was ∼2000 to 15, 000-fold higher than that of flow cytometry assays. Using the SERS assay, we demonstrate that the aggregation of hPSC-based cardiomyocyte differentiation cultures into 3D spheres significantly reduced SSEA-5 + and TRA-1-60 + cells compared with parallel 2D cultures. Thus, SERS may provide a powerful new technology for quality control of hPSC-derived products for preclinical and clinical applications.